Evaluation of scientific production in higher education using Scopus and Scimago: An analysis of the visibility and impact of educational publications - Jose, Mendoza Velazco Derling; Moscoso-Zea, Oswaldo (Edelweiss Applied Science and Technology, 2024)
This study investigates the effectiveness of the Scopus and Scimago platforms. Analysis of the evaluation of university scientific production at the National University of Chimborazo (UNACH). A focus study was applied to improve the visibility and impact of educational publications. The perceptions and experiences of 25 teachers were analyzed through qualitative interviews. The main objective was to generate a theoretical approach that conceptualizes the effective use of the Scopus and Scimago platforms for the evaluation of scientific production, identifying their advantages, disadvantages and challenges in the context of UNACH. Semi-structured interviews were applied to 25 UNACH professors. The data were coded and analyzed using Atlas.ti version 24 software. Categories, codes, dimensions and subdimensions emerging from the testimonies were identified. The results revealed three main categories: "Visibility of Publications", "Technical and Training Challenges" and "Impact on Research". The professors highlighted that Scopus offers greater visibility and academic recognition, while Scimago has limitations in the analysis of citations and access. Technical and training barriers were identified, as well as a need for greater training and institutional support. The study concluded that, although Scopus and Scimago are valuable tools for the evaluation of scientific production. Improved training and institutional support are essential to maximize their effectiveness. In addition, it is recommended to consider Scopus Preview for up-to-date analyses and comparative studies to get a more complete view of studies.